Effect of Bis [benzyl N'-(indol-3-ylmethylene)-hydrazinecarbodithioato]-zinc(II) derivatives on wound healing in Sprague Dawley rats - Mughrabi, F.F.; Hashim, H.; Ameen, M.; Khaledi, H.; Ali, Hapipah Mohd; Ismail, S. (NISCAIR, 2011)
Effects of topical application of Bis[benzyl N′-(indol-3-ylmethylene)-hydrazinecarbodithioato]-zinc(II) (BHCZ) on wound healing and histology of healed wound were assessed. Sprague Dawley rats were experimentally induced wound in the posterior neck area. Tween 20 (0.2 ml of 10%) was applied to rats in Group 1 (negative control). Intrasite gel (0.2 ml) was applied topically to rats in Group 2 as reference. BHCZ at the concentrations 0.2 ml of 25, 50 and 100 mg/ml were applied to Group 3, 4 and 5, respectively. Wound dressed with BHCZ significantly healed earlier than those treated with 10% Tween 20. Also wound dressed with 100 mg/ml BHCZ accelerated the rate of wound healing compared to those dressed with intrasite gel and, 25 mg/ml and 50 mg/ml BHCZ. Histological analysis of healed wound with BHCZ showed comparatively less scar width at wound enclosure and the healed wound contained less macrophages and large amount of collagen with angiogenesis compared to wounds dressed with 10% Tween 20. Results of this study showed that wounds dressed with 100 mg/ml of BHCZ significantly enhanced acceleration of the rate of wound healing enclosure, and histology of healed wounds showed comparatively less macrophages and more collagen with angiogenesis.